Emergency department admissions induced by drug-drug interactions in the elderly: A cross‐sectional study - Louis Letinier; Iris Pujade; Perrine Duthoit; Grégoire Evrard; Francesco Salvo; Cédric Gil‐Jardine; Antoine Pariente (Wiley, 2022)
Abstract The elderly people are increasingly exposed to polymedication and therefore to the risks of drug-drug interactions (DDIs). However, there are few data available on the clinical consequences of these drug combinations. We investigated the impact of the various DDIs classified as severe in terms of emergency admissions in the elderly. A cross‐sectional study was conducted using information from the emergency department admissions of Bordeaux University Hospital between September 2016 and August 2017. Events of interest were frequency of concomitant uses of interacting drugs that are contraindicated or warned against and frequency of emergency admissions due to contraindicated or warned against concomitant uses of interacting drugs. Five thousand, eight hundred sixty (5860) admissions to the emergency department were analyzed. A total of 375 (6.4%) contraindicated or warned against concomitant uses were identified, including 163 contraindicated (43.5%) and 212 warned against (56.5%). Reason for admission appeared likely related to the underlying DDI in 58 cases. Within these, 36 admissions were assessed as probably due to a DDI (0.6% of hospitalizations) and 22 as certainly (0.4% of hospitalizations). Of these, there were 24 (45%) admissions related to a long QT syndrome (LQTS), nine (16%) related to a drug overdose, and eight (14%) related to a hemorrhage. An antidepressant was involved in 22 of the 24 cases of LQTS. Seven of the eight cases of hemorrhage involved the antithrombotic agents / non‐steroidal anti‐inflammatory drugs combination. Elderly patients admitted to emergency departments are particularly exposed to high‐risk potential DDIs. These drug combinations lead mainly to LQTS and involve certain antidepressants.